Do children with Wilson's disease have distinct craniofacial morphology? A cephalometric study - Kılıç, Nihat; Sümbüllü, Muhammed Akif; Ertekin, Vildan; Çatal, Gülhan; Çakur, Binali; Oktay, Hüsamettin; Selimoğlu, Mukadder Ayşe (Elsevier Ireland Ltd, 2013)
Objectives: Patients with Wilson's disease (WD) develop osseous changes such as osteoporosis, spontaneous fractures, areas of sclerosis and demineralization of maxillary and mandibular bones, and neurologic symptoms including swallowing dysfunctions, which may affect dento-facial growth. However, dento-maxillo-facial structures of these patients have never been investigated. The present study aimed to discover if subjects with WD have different dentofacial structures. Methods: Lateral cephalometric films of 13 children (5 males and 8 females) with WD and of 15 normal subjects (6 males and 9 females) were evaluated. Mean ages of the patients and controls were 12.62 +/- 3.09 years and 12.01 +/- 1.38 years, respectively. Lateral cephalometric cranial films of all subjects were taken in the same cephalostat in a habitual and unstrained body posture. Thirteen linear and 11 angular parameters were measured to describe the craniofacial characteristics of the subjects. Results: Statistical analysis showed that there is no statistically significant difference between parameters of normal children and children with WD, with the exception of palatal plane inclination. The inclination of palatal plane was higher in children with WD than in normal subjects. Conclusions: Children with WD and healthy children have approximately the same dento-maxillo-facial structures. However, increased palatal plane inclination may be a finding of WD.
WOS: 000322417900011
PubMed ID: 23759337
Keywords: Cephalometry; Craniofacial Features; Wilson's Disease